1 week 1 story: Bulletin of School of Information Science UiTM Sarawak, October 2024 - February 2025 - Halamy, Suhaida; Ibrahim, Imilia; Salji, Mohd Rafiz; Mohd Jawi, Abdul Ismail; Jamil, Nurul Huda Izzati; Abdul Samad, Sabariah; Sulaiman, Sharin; Zaini, Favilla; Jack, Suriani; Bibi, Zainon (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2025)
In the name of Allah, the Most Gracious and Most Merciful. Assalamualaikum Warahmatullahi Wabarakatuh… Alhamdulillah, the School of Information Science UiTM Sarawak is excited to present the latest edition of our publication, One Week One Story Vol. 3, Issue No. 1, for this year. This new volume reflects our continued effort to highlight our students' and lecturers' creativity, hard work, and dedication. Each issue helps us create a platform that celebrates our academic and extracurricular achievements while building a sense of community. We are proud to share this edition and look forward to the contributions it will make to our collection of stories. I want to thank Dr. Susan Hydra Sikayu, the Head of the Study Centre, for her strong support and to all the lecturers and students of the School of Information Science for their meaningful contributions to this issue of One Week One Story. Your enthusiasm, creativity, and willingness to share your experiences make this publication special. Each story shared adds to the rich tapestry of our school's journey, reflecting the hard work and dedication of everyone involved. By working together, we can continue documenting the essence of our school’s vibrant community and ensure that these moments are preserved for years to come. Dear readers, I hope you enjoy this edition and thank you for your ongoing support and loyalty.